The Main Techniques of Translating Non-equivalent Words (Mongolian Journal of Humanities and Social Sciences, 2023)
The technological advances are occurring at a rapid pace in the 21st century which is called the age of information technology. Regarding these advancements, many new foreign words are entering Mongolian language constantly. Especially since 1990, the challenge has been how to translate new words, phrases and terms into Mongolian accurately from English, the main international academic language. In terms of lexical equivalence, it can be complete and partial. The issue is partial equivalence outnumbers absolute equivalence in any language depending on the cultural differences of speakers of a source language. In order to translate those non-equivalent vocabulary items, the main translation techniques such as transliteration, transcription, calque or loan translation, substitution and description are used individually and collectively. In the past, we used to spell and translate any foreign word from Russian into Mongolian as they were spelt in Russian irrespective of its pronunciation. But in the last 30 years we have been translating non-equivalent vocabulary from English into Mongolian by the main techniques mentioned above. Therefore, in the future, there is a necessity of choosing and using the best translated version of a foreign word, phrase and terms after the translation of each and every foreign word is being checked carefully. Дүйцэлгүй үгсийг орчуулах үндсэн аргуудХураангуй: Мэдээллийн эрин үе болох XXI зуунд техник, технологийн дэвшил нэн хурдацтай өрнөж байна. Үүнтэй холбоотойгоор олон үг харь хэлнээс монгол хэлэнд тогтмол орж ирж буй. Ялангуяа 1990 оноос хойш дэлхийн шинжлэх ухааны зонхилох хэл болсон англи хэлнээс монгол хэлэнд шууд орж ирж буй шинэ үг, хэллэг, нэр томьёог монгол хэл рүү хэрхэн оновчтой хөрвүүлэх нь тулгамдсан асуудал юм. Үгийн сангийн хувьд орчуулгын тохироог бүрэн ба заримдаг хэмээн ялган үзвэл бүрэн тохироот үгс аль ч хэлний үгийн сангийн цөөн хувийг эзэлнэ. Эх хэлээр харилцагсдын соёл, ахуйн ялгаанаас хамааран орчуулгын хэлэнд үгийн сангийн үлдэх хувь буюу ихэнх нь орчуулгын бүрэн биш тохироонд хамаардаг. Иймд уг өгүүлэлд дүйцэлгүй буюу эквивалентгүй үгсийг оновчтой орчуулахад эзэмших шаардлагатай орчуулгын үндсэн аргуудыг авч үзэв. Түлхүүр үг: Реали, үсэглэх, галиглах, тайлбарлах, хуулбарлан орчуулах, ойролцоо орчуулга